2008
DOI: 10.1152/ajpgi.90452.2008
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase D1 mediates NF-κB activation induced by cholecystokinin and cholinergic signaling in pancreatic acinar cells

Abstract: Yuan J, Lugea A, Zheng L, Gukovsky I, Edderkaoui M, Rozengurt E, Pandol SJ. Protein kinase D1 mediates NF-B activation induced by cholecystokinin and cholinergic signaling in pancreatic acinar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 61 publications
8
62
0
1
Order By: Relevance
“…NF-κB is one of several key signaling systems that mediate the production of proinflammatory signals in acute pancreatitis [36]. Our study confirmed that NF-κB activity in KCs is upregulated in rats with SAP, implying that NF-κB signaling of KCs is one of the events in pancreatitis.…”
Section: Discussionsupporting
confidence: 81%
“…NF-κB is one of several key signaling systems that mediate the production of proinflammatory signals in acute pancreatitis [36]. Our study confirmed that NF-κB activity in KCs is upregulated in rats with SAP, implying that NF-κB signaling of KCs is one of the events in pancreatitis.…”
Section: Discussionsupporting
confidence: 81%
“…1) In the in vitro model, isolated pancreatic acini recapitulate the initial responses (i.e., inappropriate intracellular activation of zymogens) in acute pancreatitis when treated with supraphysiological concentrations of Cer or muscarinic agonists (Carb), without the influence of inflammation, nerves, or decreased blood flow. 2) In the in vivo model, Cer hyperstimulation consistently causes mild-to-moderate pancreatitis responses, including inflammation and vascular injury (6,32,38).…”
Section: Discussionmentioning
confidence: 99%
“…PKD was shown to function downstream of PKCδ and PKCε in pancreatic acinar cells stimulated by CCK-8. Specifically, PKD was necessary for NF-κB activation induced by these GPCR agonists in pancreatic cells (111). These results identify PKD as a novel element in the signaling pathways mediating NF-κB activation in acute pancreatitis.…”
Section: Pkd Signaling In Disease: Inflammatory Responses Cardiac Hymentioning
confidence: 99%